The Routledge handbook of Indian Buddhist philosophy - Edelglass, William; Harter, Pierre-Julien; McClintock, Sara (Routledge, 2023)
"The Routledge Handbook of Indian Buddhist Philosophy is an outstanding reference source to the principal philosophers in the diverse Buddhist traditions of India, from the early Pāli writings to the twentieth century. The Handbook provides thorough coverage of the most significant figures, texts and debates that animate Buddhist philosophy. A key feature is the attention given to the ideas and works of particular Buddhist thinkers, placing the author at the centre of inquiry. Forty chapters by an international team of contributors are divided into eight clear sections, each of which includes an introduction by the editors: Buddhas as Philosophers Poet Philosophers Abhidharma Philosophers Philosophical Founders Early Period Philosophical Commentators (fifth - eighth century) Middle Period Philosophical Commentators (eighth - ninth century) Late Period Philosophical Commentators (tenth - twelfth century) Modern Philosophers. Essential reading for students and researchers in Eastern and comparative philosophy and especially Buddhist philosophy, The Routledge Handbook of Indian Buddhist Philosophy will also be of interest to those studying Buddhism in religious studies and related subjects"--
Includes bibliographical references and index
Keywords: Ideengeschichte; Buddhistische Philosophie; Indien; Buddhism / Philosophy; Buddhism / India; Buddhist philosophy; Aufsatzsammlung